Neurodevelopmental and behavioural paediatrics. (January 2015) - McDowell, Michael
Abstract One of the notable shifts in Paediatrics across the last 50 years has been towards disorders that are chronic and qualitative in nature. In addition to physical health, these impact on childhood development, behaviour and wellbeing. Understanding and management of these problems extends the traditional biological toolkit of paediatrics into the complexities of uncertainties of psychological and social context. In Australasia, the profession has responded with the development of Community Paediatrics as a recognised sub‐specialty, of which Neurodevelopmental and Behavioural Paediatrics is an important component. These developments are reviewed along with consideration of future challenges for this field of health care.